1987
DOI: 10.1104/pp.85.4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salinity on Leaf Gas Exchange in Two Populations of a C4 Nonhalophyte

Abstract: Gas exchange measurements were made on plants from two natural populations differing in salt tolerance of Axdropogon glomeratus, a C4 nonhalophyte, to examine the effect of salinity on components responsible for differences in photosynthetic capacity. Net CO2 uptake and stomatal conductance decreased with increasing salinity in both populations, but to a greater extent in the inland (nontolerant) population. The intercellular CO2 concentrations increased with increasing salinity in the inland population, but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…A similar relationship between stomatal conductance and CO 2 assimilation rate was observed in most of the canola lines examined in the present study. These results can be related to other findings on cotton , sunflower , Andropogon glomeratus (Bowman, 1987), and faba beans (Melesse & Caesar, 1992) that stomatal conductance is not always associated with CO 2 assimilation rate. This suggests that salt stress affects Pn not only due to its effects on stomatal regulation but also due to other non-stomatal effects such as ultrastructural damage and decrease in chlorophyll content below a threshold level (Melesse & Caesar, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…A similar relationship between stomatal conductance and CO 2 assimilation rate was observed in most of the canola lines examined in the present study. These results can be related to other findings on cotton , sunflower , Andropogon glomeratus (Bowman, 1987), and faba beans (Melesse & Caesar, 1992) that stomatal conductance is not always associated with CO 2 assimilation rate. This suggests that salt stress affects Pn not only due to its effects on stomatal regulation but also due to other non-stomatal effects such as ultrastructural damage and decrease in chlorophyll content below a threshold level (Melesse & Caesar, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…low temperature chamber the response of photosynthesis to changes in the intercellular partial pressure of CO 2 (pJ was measured in four plants from both chambers for the Triangle T population. This technique is useful for determining stomatal vs. nonstomatal (biochemical, biophysical) factors involved in decreasing potential photosynthesis (Farquhar and Sharkey, 1982), and has been used to assess the effect ofstress and growth temperatures on photosynthesis in other C 4 plants (Monson, Littlejohn, and Williams, 1983;Bowman, 1987;Sage and Pearcy, 1987).…”
Section: Methodsmentioning
confidence: 99%
“…This is a common response by matty plants once the salinity threshold for that specws has been readied (Maas 1986). Bowman (1987) showed that increasmg salinity decreased both stomatal conductance and net CO: uptake o f a marsh and inland C4 nonhaloplgrte grass. He went on to show that water use efB den^ decreased with increasing salinity fiir the inland population and remained the same fi)r the marsh population.…”
Section: Plant Response To Salinitymentioning
confidence: 98%